Le va-et-vient entre le polonais et le français en atelier de la créativité langagière - Blachowska-Szmigiel, Marzena; Moreau, Anne-Claire (AMU Press, 2011)
The aim of this paper is to answer the question of whether the use of the Polish language by students during the workshops of creative language behaviors in philological studies hinders or facilitates students’ learning of French as a foreign language. In the first part of the paper, we specify the properties of creative language behaviors and their development in the learners of French as a foreign language, then we characterize the creative language behavior workshops organized for our students of French as a foreign language, and finally we discuss the results of our research concerning the use of the Polish language by students during the above-mentioned workshops.
Shuttling between Polish and French in the Workshops of Creative Language Use